Effects of piston crown profiles on performance of a gasoline homogeneous charge compression ignition engine using computational fluid dynamics - Jasim, Hassan Abdulhadi (2016)
Homogeneous charge compression ignition (HCCI) combustion incorporates the advantages of both spark-ignition (SI) engines and compression ignition (CI) engines. The homogeneous mixture is inducted into the cylinder without throttling losses and compressed until the mixture reaches the auto-ignition point, and combustion then occurs spontaneously without discernible flame propagation. This feature helps to reduce emission levels while producing a relatively high thermal efficiency. In the present study, the first objective is to analyse the performance of HCCI engine with different piston crown profiles using computational fluid dynamic (CFD) method, where the software is commercially known as ANSYS FLUENT. The second objective is to evaluate the most suitable piston crown profile to be used in the gasoline-fuelled HCCI engine. Using ANSYS software to create a three-dimensional CFD, the mesh creation and specific zone names with dissimilar topologies of each zone were meshed separately. FLUENT was used to model complex combustion phenomena in an HCCI engine. The validation and simulation were conducted based on an HCCI single-cylinder, four-stroke engine fuelled with gasoline at an engine speed of 1500 rpm and with a compression ratio of 11.7:1, it was then evaluated using three split injections. Combustion parameters such as cylinder pressure, temperature and heat release rate were obtained from the validation work. The CFD model yielded good results for experimental and CFD simulation. This study focuses on how different piston crown designs affect the performance of HCCI engines. Six different designs were created and evaluated through CFD analysis, where all other engine operating parameters were the same as in the experimental work. For simplicity, the pistons were named A, B, C, D, E and F. The study analyses the in-cylinder pressure, in-cylinder temperature, heat release rate, turbulent kinetic energy, turbulent dissipation rate, NOX formation, indicated mean effective pressure (IMEP) and power output of different piston designs, and it evaluates the most suitable piston to be used in HCCI engines to improve engine performance.The results demonstrate that improved piston crown design in HCCI engines can improve engine performance. All pistons in the investigation reached a peak pressure and temperature above the experiment. In piston A there is an increase of 9.6% in indicated mean effective pressure (IMEP) and 9.76% in power output compared with the experimental results, followed by pistons B, C, D, E and F, in order from highest to lowest, which was caused by higher peak pressure towards the end of combustion, leading to diffusion combustion. Piston A’s design could be used in an HCCI engine configuration to improve engine performance.